Confocal Imaging of Developing Leaves. Issue 1 (24th January 2022) - Linh, Nguyen Manh; Scarpella, Enrico
Abstract: Questions in developmental biology are most frequently addressed by using fluorescent markers of otherwise invisible cell states. In plants, such questions can be addressed most conveniently in leaves. Indeed, from the formation of stomata and trichomes within the leaf epidermis to that of vein networks deep into the leaf inner tissue, leaf cells and tissues differentiate anew during the development of each leaf. Moreover, leaves are produced in abundance and are easily accessible to visualization and perturbation. Yet a detailed procedure for the perturbation, dissection, mounting, and imaging of developing leaves has not been described. Here we address this limitation (1) by providing robust, step‐by‐step protocols for the local application of the plant hormone auxin to developing leaves and for the routine dissection and mounting of leaves and leaf primordia, and (2) by offering practical guidelines for the optimization of imaging parameters for confocal microscopy. We describe the procedure for the first leaves of Arabidopsis, but the same approach can be easily applied to other leaves of Arabidopsis or to leaves of other plants. © 2022 Wiley Periodicals LLC. Support Protocol 1 : Preparation of plant growth medium Support Protocol 2 : Preparation of growth medium plates Basic Protocol 1 : Seed sterilization, sowing, and germination, and seedling growth Support Protocol 3 : Preparation of IAA–lanolin paste Basic Protocol 2 : Application of IAA–lanolin paste to 3.5‐DAG first leaves Basic Protocol 3 : Dissection of 3‐ to 6‐DAG first leaves and leaf primordia Basic Protocol 4 : Dissection of 1‐ and 2‐DAG first‐leaf primordia Basic Protocol 5 : Mounting of dissected leaves and leaf primordia Support Protocol 4 : Quality check of mounted leaves and leaf primordia by fluorescence microscopy Basic Protocol 6 : Imaging of mounted leaves and leaf primordia by confocal microscopy